Contraceptive discontinuation among women of reproductive age in Papua New Guinea - Louis Kobina Dadzie; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Justice Kanor Tetteh; Tarif Salihu; Joshua Okyere; Sanni Yaya (BMC, 2022)
Abstract Background Papua New Guinea has one of the lowest contraceptive prevalence rates among women of reproductive age in the Western Pacific Region and this makes contraceptive discontinuation in this country a critical public health issue worth studying. This study sought to assess the factors associated with contraceptive discontinuation among women of reproductive age in Papua New Guinea. Methods The data used for the analysis were obtained from the Papua New Guinea Demographic and Health Survey which was conducted in 2016-2018. The outcome variable for this study was contraceptive discontinuation among women of reproductive age. Crude odds ratios and adjusted odds ratios with 95% confidence intervals were estimated using binary logistic regression. Results About 33.26% of the women discontinued injectables, 19.15% discontinued pills and 3.77% discontinued other contraception methods. Women aged 20-24 [aOR = 2.12, CI = [= [1.04,4.31] through to those aged 30-34 [aOR = 1.98, CI = 1.03,3.79] had higher odds to discontinue contraceptive usage compared to those aged 45-49. Women with no information on choice of contraception [aOR = 2.85, CI = 2.31,3.51], those with two or more births in the last five years [aOR = 2.35, CI = 1.65,3.35] and those living in the Highland region [aOR = 1.71, CI = 1.28,2.29] were more likely to discontinue contraceptive usage compared with those with information on contraceptive choices, those with no births and those living in the Island region respectively. However, women in the rural areas [aOR = 0.78, CI = 0.61,0.99], women using LARC [aOR = 0.10, CI = 0.06,0.15], injectables [aOR = 0.43, CI = 0.30,0.63] and other modern contraception methods including condom [aOR = 0.22, CI = 0.15,0.34] were less likely to discontinue contraceptive usage. Conclusion A nationwide mass education on the benefits of contraception is recommended for the Papua New Guinea National Department of Health to tackle the key findings of this study which were high contraceptive discontinuation prevalence with lack of information on choice, disproportionately high contraceptive discontinuation rate in the Highland Region and the desire to give birth to more than two children as some factors associated with contraceptive discontinuation in Papua New Guinea.